SPECIAL REASONS FOR JUDGES IN GRANTING MARRIAGE DISPENSATION ON THE BASIS OF NON-URGENT REASONS (Case Study of Indonesian Religious Court Stipulations) - Kusumawardhani, Rosalia; Sanjaya, Umar Haris (JOURNAL EQUITABLE, 2025)
The amendment to Article 7 of Law No. 16/2019 on Marriage, particularly Article 7 section (2), does not provide a specification of urgent reasons for applying to the Court for dispensation to marry. This condition gives Judges the flexibility to grant dispensation to marry on non-urgent grounds, as well as providing leeway for parents in their main role of preventing child marriage. The main problem to be discussed is related to the reasons for Judges to grant marriage dispensation on the basis of non-urgent reasons. The research method is normative law, which produces descriptive data in the form of written information. The data analyzed is secondary data, with a Legislation approach from PERMA Number 5 of 2019 and case studies from the 2023 determination of the Religious Courts in Indonesia. The results showed that the urgent reason is only in two situations, namely: the prospective wife is pregnant outside of marriage and has had relations as husband and wife between the two, but in fact the Judge in adjudicating marriage dispensation does not necessarily apply urgent reasons, but there are special reasons for the Judge which are used as the basis for granting marriage dispensation on a non-urgent basis.